2015
DOI: 10.1021/acsnano.5b03232
|View full text |Cite
|
Sign up to set email alerts
|

Towards 3D Mapping of BO6 Octahedron Rotations at Perovskite Heterointerfaces, Unit Cell by Unit Cell

Abstract: The rich functionalities in the ABO3 perovskite oxides originate, at least in part, from the ability of the corner-connected BO6 octahedral network to host a large variety of cations through distortions and rotations. Characterizing these rotations, which have significant impact on both fundamental aspects of materials behavior and possible applications, remains a major challenge at heterointerfaces. In this work, we have developed a unique method to investigate BO6 rotation patterns in complex oxides ABO3 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 50 publications
5
62
0
Order By: Relevance
“…The oxygen octahedra network was investigated with an atomically resolved ABF imaging technique which is capable to image both heavy cations and oxygen ions simultaneously40. Most of the previous ABF observations of oxygen octahedra in perovskite manganite layers were made in the <100> pc zone axis orientation, where the linear density of the oxygen columns is given by 1/ a , the same as the neighboring A/B cation column; a denotes the lattice parameter of the pseudo-cubic perovskite structure, further indicated by the subscript pc .…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen octahedra network was investigated with an atomically resolved ABF imaging technique which is capable to image both heavy cations and oxygen ions simultaneously40. Most of the previous ABF observations of oxygen octahedra in perovskite manganite layers were made in the <100> pc zone axis orientation, where the linear density of the oxygen columns is given by 1/ a , the same as the neighboring A/B cation column; a denotes the lattice parameter of the pseudo-cubic perovskite structure, further indicated by the subscript pc .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, by using BF-STEM resolution can be improved beyond that typically attained with HAADF-STEM (single-tilt and dual-axis ABF-STEM and BF-STEM) (Hohmann-Marriott et al, 2009;Sousa et al, 2013). HAADF-STEM is traditionally used for applications in the field of materials science (Okunishi et al, 2012;He et al, 2015;Nakamura et al, 2015), and can provide diffraction limited sub-Angstrom imaging of radiation resistant samples, but more recently also been explored by biomedical researchers for imaging thick sections of tissues or cells, and because the BF-and HAADF-STEM signals are collected simultaneously, the information the two separate detectors collect can be reconstructed (Hohmann-Marriott et al, 2009). Hohmann-Marriott et al compared STEM-HAADF and STEM-BF reconstructed data sets, and demonstrated that the resolution in both were comparable for the majority of the reconstructed volume, except as predicted along the bottom where BF was superior to HAADF (Hohmann-Marriott et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, solid/solid interfaces are often the starting point of extended defects such as misfit dislocations that arise to compensate epitaxial strain, and lead to elastic fields propagating in both directions from the interface, substantially modifying its crystal structure and potentially its properties. It has also been demonstrated that, even for a case of coherent epitaxy, the different symmetry of the film and substrate can result in a progression of distinct structural states localized in the vicinity of the interface [31]. In all these instances, it is crucial to precisely extract and identify the local structural states present at interfaces.…”
Section: Resultsmentioning
confidence: 99%